2021
DOI: 10.1016/j.foodhyd.2020.106134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structure and properties of hydroxypropylated acid-hydrolysed maize starches with different amylose/amylopectin contents

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…( 2006 ) also reported that an increase in etherifying agents led to an increase in cassava starch MS. Similar results were observed by other researchers on maize starches (Chen et al., 2021 ). Rutkaitė et al.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…( 2006 ) also reported that an increase in etherifying agents led to an increase in cassava starch MS. Similar results were observed by other researchers on maize starches (Chen et al., 2021 ). Rutkaitė et al.…”
Section: Resultssupporting
confidence: 92%
“…Chen et al. ( 2021 ) reported a reduction in gelatinization temperature and enthalpy in dually modified maize starches modified by acid hydrolysis and hydroxypropylation. Lee and Yoo ( 2011 ) reported that hydroxypropylated sweet potato starches had lower gelatinization temperatures and enthalpy than native starch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the MS of water-soluble HPS samples was calculated according to the standard curve. The specific operation method was as follows (Chen et al 2021): 1g of propylene glycol solution was added into a 1000 mL volumetric flask, then diluted with distilled water to the specified scale. Subsequently, 1, 2, 3, 4, and 5 mL of the above solution was added into five 100 mL volumetric flask, respectively, and diluted with distilled water to the specified scale, to obtain series of standard solutions with propylene glycol content of 10, 20, 30, 40, 50 μg/ml, respectively.…”
Section: Determining the Molar Substitution (Ms) And Reaction Efficiementioning
confidence: 99%
“…Starch is the most accessible biomass resource, starch utilization has been a focus of ongoing research. Natural starch has the disadvantages of poor water solubility, low degree of emulsification and gelatinization, and low stability, which limits the application range of natural starch in various industries (Kim et al, 2017 ; Remya et al, 2018 ; Escobar-Puentes et al, 2020 ; Chen et al, 2021 ). Therefore, modified starches are prepared by introducing new or changing functional groups through physicochemical and biological modifications to equip starch with new characteristics (Sangian et al, 2018 ; Xiao et al, 2018 ; Li et al, 2020 ; Menzel, 2020 ; Torbica et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%